Orthodontic anchorage in edentulous areas - a finite element analysis - Lizaso, Arlyn Ang
Despite advances in caries prevention and periodontal disease treatment, tooth loss and the edentulous stare remains a significant health care issue, such that a number of patients presenting for orthodontic treatment are already partially edentulous. The aim of this study is to perform finite element analysis to determine the stress distribution of miniscrews embedded in edentulous areas in order to ascertain the possibility of attaining primary stability on these areas.
The present study found that all miniscrews embedded in mandibular edentulous specimens were able to establish primary stability except for 2 scenarios in MdE4. 12-13% of miniscrews embedded on maxillary edentulous specimen were not able to establish primary stability. Majority of these occurred with screw diameter of 1.5mm. (78-85%), exposed screw length jof 5mm. (61-72%), force magnitude of 6 N. (62-68%), and force angle of 90° (40-45%).
Based on the data gathered, it is found that placement of orthodontic miniscrew on edentulous alveolar bone on both the maxilla and mandible is possible. The use of miniscrew with diameter of 2mm. or wider embedding it on attached gingival of 2 mm. or thinner, loading it with force 2 N. or lower at an angle 60 or 120° could increase chances of establishing primary stability.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Orthodontics; Orthodontic miniscrews